Pengaruh kualitas interaksi atasan-bawahan dan dukungan organisasional persepsian terhadap organizational citizenship behavior foci supervisor dan organisasi - Syahrizal, Syahrizal; Mesta, Hendri Andi; Fitria B, Fadhilatul (Jurusan Manajemen Fakultas Ekonomi Universitas Negeri Padang, 2018)
The purpose of this research is to analyze (1) the influence of leader member exchange on Organizational Citizenship Behavior Foci Supervisor (2) the influence of perceived organizational support on Organizational Citizenship Behavior Foci Supervisor (3) the influence of leader member exchange on Organizational Citizenship Behavior Foci organizational (4) the influence of perceived organizational support on Organizational Citizenship Behavior Foci organizational. The populations in this research are the employees of PT. Telekomunikasi Padang which consist of 128 employees. The samples were selected using Clustered Proportional Sampling which the total of the samples are 97 employees. The data used are primary data and secondary data. The data was analyzed using multiple reggression analysis. The result of this research shows (1) leader member exchange has a positive relationship onÂ Organizational Citizenship Behavior Foci Supervisor (2) perceived organizational support has a positive relationship onÂ Organizational Citizenship Behavior Foci Supervisor (3) leader member exchange has a positive relationship on Organizational Citizenship Behavior Foci organizational (4) perceived organizational support has a positive relationship onÂ Organizational Citizenship Behavior Foci organizational.Keywords: Organizational citizenship behavior foci supervisor (OCBS); perilaku kewarganegaraan organisasi foci organisasional (OCBO), pertukaran anggota pemimpin; dukungan organisasi persepsi